On Selection of Components for a Diffusion Index Model: It's not the Size, It's How You Use It - Boriss Siliverstovs; Konstantin Arkadievich Kholodilin (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper suggests a novel approach to pre-selection of the component series of the diffusion index based on their individual forecasting performance. It is shown that this targeted selection allows substantially improving the forecasting ability compared to the diffusion index models that are based on the largest available data set.
Keywords: C10; E32; 330; Diffusion index; forecasting; optimal subset of data